Serfdom, society, and the arts in imperial Russia : the pleasure and the power - Stites, Richard, 1931-2010 (Yale University Press, 2005)
Richard Stites explores the dramatic shift in the history of visual and performing arts that took place in the last decades of serfdom in Russia in the 1860s and revisualises the culture of that flamboyant era.